Parental Emotion Socialization and Child Psychological Adjustment among Chinese Urban Families: Mediation through Child Emotion Regulation and Moderation through Dyadic Collaboration - Jin, Zhuyun; Zhang, Xutong; Han, Zhuo Rachel (Frontiers in Psychology, 2017)
The theoretical model of emotion regulation and many empirical findings have suggested that children’s emotion regulation may mediate the association between parents’ emotion socialization and children’s psychological adjustment. However, limited research has been conducted on moderators of these relations, despite the argument that the associations between parenting practices and children’s psychological adjustment are probabilistic rather than deterministic. This study examined the mediating role of children’s emotion regulation in linking parents’ emotion socialization and children’s psychological adjustment, and whether dyadic collaboration could moderate the proposed mediation model in a sample of Chinese parents and their children in their middle childhood. Participants were 150 Chinese children (87 boys and 63 girls, M age = 8.54, SD = 1.67) and their parents (M age = 39.22, SD = 4.07). Parent-child dyadic collaboration was videotaped and coded from an interaction task. Parents reported on their emotion socialization, children’s emotion regulation and psychopathological symptoms. Results indicated that child emotion regulation mediated the links between parental emotion socialization and child’s psychopathological symptoms. Evidence of moderated mediation was also found: supportive emotion socialization and child emotion regulation were positively correlated only at high and medium levels of dyadic collaboration, with child’s psychopathological symptoms as the dependent variables. Our findings suggested that higher-level parent-child collaboration might further potentiate the protective effect of parental supportive emotion socialization practices against child psychopathological symptoms.